Phase change energy storage composite coating with photo-thermal and electric heating functions, preparation method of phase change energy storage composite coating and application of phase change energy storage composite coating in all-weather anti-icing and deicing
By integrating phase change materials and photothermal conversion carriers, a phase change energy storage composite coating with both photothermal and electric heat is prepared, which solves the problem that the existing photothermal superhydrophobic surface cannot effectively resist ice and deicing in the night and cloudy days, and achieves active deicing effect and efficient energy utilization all-weather.
Patent Information
- Application Number
- CN202411858186.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The existing photothermal superhydrophobic surface cannot effectively resist ice and deicing during nights, cloudy days and other periods, and the energy utilization rate of photothermal conversion is not high, resulting in limited delayed icing effect.
By integrating phase change materials (PCMs) and photothermal conversion carriers, a phase change energy storage composite coating with both photothermal and electric heat is prepared. This coating realizes the combination of photothermal and phase-change energy storage by coating the molded phase-change energy storage layer, applying copper foil, coating the electrothermal and electrothermal energy storage layer, and coating the molded photothermal and superhydrophobic energy storage coating, improving solar energy utilization efficiency, and maintaining an effective anti-ice and deicing function through the electrothermal energy storage layer at night or cloudy days.
It realizes the active deicing effect all-weather, can effectively prevent icing under extreme climatic conditions, and maintains effective anti-icing deicing function during nights, cloudy days and other periods, improving energy utilization efficiency and delaying icing effect.
Smart Images

Figure CN119684894A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of phase change functional materials, and in particular to a phase change energy storage composite coating having both photothermal and electrothermal properties, a preparation method thereof, and all-weather anti-icing and de-icing applications. Background Art
[0002] Traditional anti-icing and de-icing technologies mainly rely on mechanical or chemical methods, such as the use of de-icing agents or mechanical scraping to remove ice and snow, but these methods have problems such as low efficiency, high energy consumption, and environmental pollution. In recent years, with the development of new material technology, super-hydrophobic coating materials based on photothermal or electrothermal conversion technology have gradually become a green, environmentally friendly, and low-energy anti-icing and de-icing solution. These materials combine the principles of photothermal or electrothermal conversion to use light energy or electrical energy to increase the surface temperature of the material, thereby preventing the formation of ice or quickly melting the ice layer that has formed. At the same time, the super-hydrophobic property can reduce the chance of water droplets adhering to the surface, further enhancing the anti-icing effect. This multifunctional coating material can self-regulate the surface temperature, reduce energy consumption, and has broad application prospects.
[0003] At present, combining photothermal characteristics with super-hydrophobic surfaces is a new idea to improve ice resistance and deicing. Chinese patent application CN114058224A discloses a photothermal responsive super-hydrophobic anti-icing composite coating and its preparation method. The preparation method applies silicone rubber on the surface of the substrate, then disperses micron-sized particles and nano-sized particles in a solvent to obtain a uniform dispersion, obtains a coating on the substrate by spraying, and finally obtains a photothermal responsive super-hydrophobic anti-icing composite coating through heat treatment and fluorination treatment. Chinese patent CN 116790186 B discloses an environmentally friendly super-hydrophobic anti-icing and de-icing material with efficient photothermal conversion and a preparation method thereof. The method firstly combines a two-dimensional sheet material with photothermal response and nanoparticles with photothermal response closely together through the in-situ action of gradient reduction; then the composite photothermal conversion material is coated on the surface of a substrate with a three-dimensional columnar array structure together with a hydrophobic modifier, and the photothermal conversion is carried out after light absorption is promoted by the hydrophobicity of the coating and the multiple reflections of the columnar array microstructure, so as to achieve an excellent photothermal response temperature of the material, and the de-icing effect is improved, which can simultaneously meet the requirements of passive anti-icing and anti-frost and active de-icing and defrosting. Environmentally friendly photothermal materials use solar energy to enhance the anti-icing and active de-icing and defrosting effects, but the coating cannot effectively resist ice and de-icing at night, cloudy days and other time periods, that is, it cannot achieve all-weather anti-icing and de-icing; in addition, the effect of delaying ice formation by combining photothermal characteristics with super-hydrophobic surfaces is limited, and the energy converted from photothermal is easily lost in the environment, thus affecting the effect of delaying ice formation, and there are problems and shortcomings of low overall energy utilization. Summary of the invention
[0004] In order to overcome the deficiencies of the prior art, the first object of the present invention is to provide a method for preparing a phase-change energy storage composite coating having both photothermal and electrothermal properties.
[0005] The present invention first prepares a photothermal phase change energy storage material by integrating phase change materials (PCMs) and photothermal conversion carriers; using the simple phase change thermal energy storage and release principle, the photothermal conversion carrier is combined with the phase change material to absorb and store heat when the light is sufficient, and release the stored energy when the light is weakened or there is no light. This characteristic gives them unique advantages in improving the efficiency of solar energy utilization and solving the problem of solar energy intermittency, effectively improving the energy utilization efficiency. Specifically, by combining microencapsulation technology, a phase change microcapsule energy storage material with high heat capacity and stable phase change characteristics was successfully prepared. Then, the Cu micro-nanoparticles with photothermal effect are in-situ reduced on the surface of the phase change microcapsule energy storage material, and the characteristics of photothermal and phase change energy storage are realized at the same time; finally, super hydrophobicity is achieved by combining surface modification and the micro-nano structure of the material. The specific material preparation method is to coat a phase change energy storage layer in sequence, paste copper foil and coat an electric thermal energy storage layer, and coat a photothermal super-hydrophobic energy storage coating to simultaneously combine photothermal, electric thermal, super-hydrophobic properties and phase change microcapsule energy storage. The utilization efficiency of solar energy is improved by combining photothermal with phase change microcapsule energy storage, and the efficiency of electricity use is also improved by combining electric thermal with phase change microcapsule energy storage. The phase change energy storage of the three coating layers effectively improves the effect of delaying icing and can achieve all-weather active deicing, to cope with surface anti-icing and deicing under extreme climatic conditions, and to ensure that the coating maintains effective anti-icing and deicing functions at night, on cloudy days and other time periods.
[0006] In order to overcome the shortcomings of the prior art, the second object of the present invention is to provide a phase-change energy storage composite coating that combines photothermal and electrothermal properties. The phase-change energy storage composite coating that combines photothermal and electrothermal properties has the advantages of low preparation cost, high anti-icing and deicing efficiency, high energy utilization rate, and good super-hydrophobic performance.
[0007] The third object of the present invention is to provide a phase-change energy storage composite coating with both photothermal and electrothermal properties for use in all-weather anti-icing and deicing.
[0008] In order to achieve the first object of the above invention, the technical solution adopted by the present invention is as follows:
[0009] The present invention provides a method for preparing a phase-change energy storage composite coating having both photothermal and electrothermal properties, comprising the following steps:
[0010] S1. Coating and forming a phase change energy storage layer: coating a slurry containing silicon dioxide-coated n-hexadecane phase change microcapsules on a substrate, and then curing and forming a phase change energy storage layer;
[0011] S2, pasting copper foil and coating an electric thermal energy storage layer: pasting copper foil electrodes on two opposite edges of the surface of the phase change energy storage layer formed in step S1 and extending them to the outside of the phase change energy storage layer, and then coating the surface of the phase change energy storage layer with a slurry containing silicon dioxide-copper double-shell coated n-hexadecane phase change microcapsules and graphite to form an electric thermal energy storage layer;
[0012] S3. Coating and forming a photothermal super-hydrophobic energy storage coating: coating the surface of the electrothermal energy storage layer formed in step S2 with a slurry containing fluorinated silica-copper double-shell-coated n-hexadecane phase change microcapsules, and then curing and forming the photothermal super-hydrophobic energy storage coating, thereby obtaining the phase change energy storage composite coating having both photothermal and electrothermal properties.
[0013] Furthermore, in step S1, a slurry containing silicon dioxide-coated n-hexadecane phase change microcapsules is coated on an aluminum plate that has been sanded and cleaned with isopropyl alcohol, and then cured to form a phase change energy storage layer; the synthesis method of silicon dioxide-coated n-hexadecane phase change microcapsules comprises the following steps:
[0014] 1) Emulsification: After heating a mixed solution of anhydrous ethanol and water, n-hexadecane, hexadecyltrimethylammonium bromide and tetraethyl orthosilicate are added to disperse and form an oil-in-water emulsion;
[0015] 2) Polycondensation reaction: adding a base to the oil-in-water emulsion obtained in step 1) to carry out a polycondensation reaction, and then filtering, washing and drying to obtain the silicon dioxide-coated n-hexadecane phase change microcapsules.
[0016] Among them, the mechanism of the emulsification step and the polycondensation step is as follows:
[0017] Hexadecyltrimethylammonium bromide is used as an emulsifier. Hexadecyltrimethylammonium bromide can ionize in water to generate hydrophilic NH 4 + , can form a strong positive electric field on the surface of n-hexadecane droplets, thereby improving the dispersion stability of the emulsified system and the enrichment capacity of small molecules of the wall material, so that the obtained water-in-oil emulsion is stable and does not stratify. In addition, during the polycondensation reaction, under alkaline conditions, OH - Directly nucleophilically attack the central silicon atom, with negatively charged OH - The electron cloud of tetraethyl orthosilicate is shifted to the -OR side, resulting in the breaking of the silicon-oxygen bond and the occurrence of a hydrolysis reaction. When one -OR is hydrolyzed, the Si atom is positively charged, making the hydrolysis reaction easier to occur, making the hydrolysis rate of tetraethyl orthosilicate faster and more complete. After hydrolysis, silicic acid and silicic acid, and silicic acid and tetraethyl orthosilicate will undergo polycondensation to form tiny crystal nuclei. The subsequent hydrolysis products continue to grow and deposit on the surface of the crystal nucleus, eventually forming SiO 2 The shell layer is coated with n-hexadecane. Among them, the hydrolysis and condensation of tetraethyl orthosilicate into SiO2 The reaction principle is shown in Formula I:
[0018]
[0019] Furthermore, in the emulsification step, the volume ratio of the anhydrous ethanol to water is 1:(1.5-3); the mass ratio of n-hexadecane, hexadecyltrimethylammonium bromide and tetraethyl orthosilicate is (8-12):(1-2.5):(10-15); the mass volume ratio of n-hexadecane to the mixed solution is (8-12) g:(250-300) mL; the heating is performed by heating to 30°C-40°C in a water bath; the dispersion is performed by stirring at a speed of 2000 rpm-3000 rpm for 5 min-15 min using a high-speed disperser; and / or
[0020] In the polycondensation reaction step, ammonia water with a mass concentration of 25%-28% is added to the water-in-oil emulsion obtained in the emulsification step at 30°C-40°C for polycondensation reaction for 22h-26h, then filtered, washed with petroleum ether and anhydrous ethanol for 2-4 times respectively, then washed with clean water for 1-3 times, and then freeze-dried for 22h-26h to obtain a white powder product, which is the silicon dioxide-coated n-hexadecane phase change microcapsule; the volume ratio of the alkali to the water-in-oil emulsion is (1-5): (250-350).
[0021] Furthermore, in step S2, the synthesis method of the silicon dioxide-copper double-shelled n-hexadecane phase change microcapsules comprises the following steps:
[0022] 1) Sensitization: to SnCl 2 After adding hydrochloric acid to the solution and mixing, adding the silicon dioxide-coated n-hexadecane phase change microcapsules prepared in step S1 to react, thereby obtaining sensitized phase change microcapsules;
[0023] 2) Activation: Add the sensitized phase change microcapsules to PdCl 2 An activation reaction is carried out in the solution, and after filtration and washing, activated phase change microcapsules are obtained;
[0024] 3) Chemical copper plating: The activated phase change microcapsules, copper sulfate pentahydrate and EDTA are added into water, and then sodium hypophosphite is added under stirring to carry out chemical copper plating reaction, so as to obtain the silicon dioxide-copper double shell layer coated n-hexadecane phase change microcapsules.
[0025] Among them, SnCl 2 The sensitization mechanism is as follows: In SnCl 2 In solution, Sn 2+ (Stannic ions) react with the hydroxyl (-OH) adsorption site of the silica shell to form a layer of Sn(OH) 2Thin film. At the same time, some Sn 2+ In the air, it will be oxidized to Sn 4+ , thereby generating Sn on the substrate surface 2+ / Sn 4+ Mixed state. This mixed state film has strong adsorption and can well adsorb the subsequent activator Pd 2+ .
[0026] Among them, PdCl 2 The activation mechanism is as follows: 2 In solution, Pd 2+ It will undergo redox reaction with the sensitized Sn layer. 2+ Pd 2+ Reduced to metal Pd with catalytic activity. The ion reaction equation is shown in Formula II:
[0027] Sn 2+ +Pd 2+ =Pd+Sn 4+
[0028] Formula II.
[0029] Then, metallic Pd is deposited on the SiO 2 On the surface of the shell substrate, these nano Pd particles act as active catalytic centers, providing the required active sites for the subsequent self-catalytic chemical copper plating. Under the catalysis of nano Pd particles, the sodium hypophosphite reduces the copper ions for plating, and the reaction equation is shown in Formula III:
[0030]
[0031] Furthermore, in the sensitization step, SnCl with a mass concentration of 0.5%-1.5% is added. 2 Add 9 mol / L-12 mol / L hydrochloric acid to the solution, stir at 250 rpm-350 rpm for 3 min-8 min to mix, add the silicon dioxide coated hexadecane phase change microcapsules in step S1, stir and react for 5 min-15 min, then filter and wash 2-4 times to obtain sensitized phase change microcapsules; the silicon dioxide coated hexadecane phase change microcapsules, SnCl 2 The mass volume ratio of the solution and hydrochloric acid is (3-8) g: (90-110) mL: (3-5) mL; and / or
[0032] In the activation step, the sensitized phase change microcapsules are reacted with PdCl 2 The mass volume ratio of the solution is (0.5-1.5) g: (40-60) mL; the PdCl 2The concentration of the solution is 40 mg / L-60 mg / L, and the activation time is 3 min-8 min; and / or
[0033] In the chemical copper plating step, the mass volume ratio of the copper sulfate pentahydrate, EDTA, activated phase change microcapsules, sodium hypophosphite and water is (1-3) g: (0.5-2) g: (1-3) g: (2-4) g: (90-110) mL; the stirring speed is 150 rpm-250 rpm; and the chemical copper plating reaction time is 50 min-70 min.
[0034] Further, in step S3, the synthesis method of the fluorinated silica-copper double-shell n-hexadecane phase change microcapsules is as follows: micro-etching the surface of the silica-copper double-shell n-hexadecane phase change microcapsules with a micro-etching solution, dissolving tridecafluorooctyl triethoxysilane in anhydrous ethanol, and then adding the micro-etched silica-copper double-shell n-hexadecane phase change microcapsules, stirring and dispersing, and then adding deionized water, stirring and hydrolyzing for 1.5h-2.5h, filtering and washing with ethanol, and then placing in a vacuum drying oven at 75°C-85°C for 3h-5h; and / or
[0035] The mass volume ratio of tridecafluorooctyl triethoxysilane, ethanol, silicon dioxide-copper double shell coated hexadecane phase change microcapsules, and water is (3-5) mL: (180-220) mL: (3-5) g: (0.3-0.8) mL; and / or
[0036] The micro-etching solution comprises sulfuric acid, hydrogen peroxide, sodium silicate and water, and the mass ratio of the sulfuric acid, hydrogen peroxide, sodium silicate and water is (5-6) g: (2-3) g: (0.05-0.1) g: (100-200) mL.
[0037] Among them, tridecafluorooctyl triethoxysilane was hydrolyzed and micro-etched with silicon dioxide-copper double shell coated with hexadecane phase change microcapsules (denoted as nC 16 @SiO 2 -Cu) surface to form a Cu-O-Si bond, and then the tridecafluorooctyl group is modified to nC 16 @SiO 2 -Cu surface. 16 @SiO 2 -Cu surface modification can increase nC 16 @SiO 2 -Surface hydrophobicity of Cu.
[0038] Furthermore, in the step S1, the phase change energy storage layer is coated: the terminal hydroxyl polydimethylsiloxane and the curing agent are added to n-hexane and stirred and mixed, and then the silicon dioxide-coated n-hexadecane phase change microcapsules are added to form the slurry, and then the slurry is sprayed and cured at 90°C-110°C for 1.5h-2.5h to form the phase change energy storage layer;
[0039] In the step S2, copper foil is pasted and an electric thermal energy storage layer is coated: copper foil electrodes are pasted at two opposite edges of the surface of the phase change energy storage layer formed in step S1 and extended to the outside of the phase change energy storage layer; terminal hydroxyl polydimethylsiloxane and a curing agent are added to n-hexane and stirred and mixed, and then silicon dioxide-copper double-shell coated n-hexadecane phase change microcapsules and graphite are added to mix to form the slurry, and then the slurry is sprayed on the surface of the phase change energy storage layer to form the electric thermal energy storage layer;
[0040] Among them, in step S2, the n-hexadecane phase change microcapsules are coated with a silica-copper double shell layer and combined with a small amount of graphite to play the role of connecting the conductive network, thereby obtaining an electrothermal energy storage coating with good electrothermal performance.
[0041] In the step S3, a photothermal super-hydrophobic energy storage coating is coated: terminal hydroxyl polydimethylsiloxane and a curing agent are added to n-hexane and stirred and mixed, and then fluorinated silica-copper double-shell coated n-hexadecane phase change microcapsules are added to form the slurry, and then the slurry is sprayed on the surface of the electrothermal energy storage layer, and then cured at 90°C-110°C for 5h-7h to form the photothermal super-hydrophobic energy storage coating, so as to obtain the phase change energy storage composite coating with both photothermal and electrothermal properties.
[0042] Furthermore, the curing agents in steps S1, S2 and S3 are all component B of Dow Corning 184;
[0043] In the step S1, the mass volume ratio of the terminal hydroxyl polydimethylsiloxane, the curing agent, the silicon dioxide-coated n-hexadecane phase change microcapsules and n-hexane is (3-4) g: (0.2-0.5) g: (0.5-1.5) g: (15-25) mL;
[0044] In the step S2, the mass volume ratio of the hydroxy-terminated polydimethylsiloxane, the curing agent, the silicon dioxide-copper double-shell coated n-hexadecane phase change microcapsules, the graphite and the n-hexane is (1.5-2.5) g: (0.1-0.3) g: (0.3-0.8) g: (0.1-0.3) g: (10-20) mL;
[0045] In the step S3, the mass volume ratio of the hydroxy-terminated polydimethylsiloxane, the curing agent, the fluorinated silica-copper double-shell coated n-hexadecane phase change microcapsules and n-hexane is (0.5-1.5) g: (0.1-0.2) g: (0.5-1.2) g: (5-15) mL;
[0046] In the step S2, the particle size of the graphite is 1 μm-5 μm.
[0047] In order to achieve the second purpose of the above invention, the technical solution adopted by the present invention is as follows:
[0048] The present invention provides a phase-change energy storage composite coating having both photothermal and electric heating properties, which is prepared by the above-mentioned method for preparing a phase-change energy storage composite coating having both photothermal and electric heating properties.
[0049] In order to achieve the third purpose of the above invention, the technical solution adopted by the present invention is as follows:
[0050] The present invention provides a method for preparing a phase-change energy storage composite coating having both photothermal and electric heating properties, and application of the prepared phase-change energy storage composite coating having both photothermal and electric heating properties in all-weather anti-icing and deicing.
[0051] A phase-change energy storage composite coating with both photothermal and electric heating prepared by the present invention is a super-hydrophobic anti-icing-deicing coating. Due to its efficient photothermal and electric heating conversion and energy storage function, it can be applied to the surface of outdoor equipment. The photothermal or electric heating conversion performance of the phase-change energy storage composite coating with both photothermal and electric heating can increase the surface temperature of the equipment to prevent icing, and its hydrophobic property can prevent the adhesion of water and ice, thereby extending the service life of the equipment. It can especially cope with the problem of surface icing under extreme climatic conditions, and ensure that the coating maintains effective anti-icing and deicing functions at night, on cloudy days, and other time periods.
[0052] Compared with the prior art, the present invention has the following beneficial effects:
[0053] (1) The present invention provides a method for preparing a phase-change energy storage composite coating having both photothermal and electrothermal properties. The method comprises the following steps: sequentially coating a phase-change energy storage layer, pasting a copper foil, coating an electrothermal energy storage layer, and coating a photothermal super-hydrophobic energy storage coating. The method combines the photothermal, electrothermal, super-hydrophobic properties, and the energy storage function of phase-change microcapsules to effectively delay ice formation. The method has the advantages of simple preparation method, high anti-icing and deicing efficiency, good photothermal conversion performance, and good super-hydrophobic performance. The method can also cope with surface anti-icing and deicing under extreme climatic conditions, ensuring that the coating maintains effective anti-icing and deicing functions at night, on cloudy days, and other time periods.
[0054] (2) The present invention discloses a method for preparing a phase-change energy storage composite coating having both photothermal and electrothermal properties. The method utilizes an interfacial polymerization method to prepare silicon dioxide-coated n-hexadecane phase-change microcapsules having a phase change enthalpy of 170 J / g. The microcapsules are nano-scale microcapsules. On the one hand, the problem of leakage of n-hexadecane during the phase change process can be avoided. On the other hand, a phase-change energy storage layer is formed by combining the silicon dioxide-coated n-hexadecane phase-change microcapsules with terminal hydroxyl polydimethylsiloxane. When the ambient temperature is lower than the phase change temperature of the phase-change material, the silicon dioxide-coated n-hexadecane phase-change microcapsules begin to solidify and release a large amount of latent heat, thereby providing heat, maintaining a high surface temperature, and preventing freezing due to excessively low temperature.
[0055] In addition, by chemically copper-plating the silicon dioxide-coated hexadecane phase change microcapsules, the copper-plated layer can achieve the effect of "killing two birds with one stone" by regulating the process: it is both conductive and has the corresponding function of light and heat, that is, it can convert sunlight into heat energy. The electrothermal energy storage layer is formed by combining the silicon dioxide-copper double shell layer to coat the hexadecane phase change microcapsules, graphite and terminal hydroxyl polydimethylsiloxane, and copper foil is used as the electrode of the electrothermal energy storage layer and the wire connected to the external current, so that the phase change energy storage composite coating has good conductivity and electrothermal performance, solves the all-weather problem, and ensures that the coating maintains effective anti-icing and deicing functions at night, cloudy days and other time periods. At the same time, the hexadecane inside the phase change microcapsules not only has a suitable phase change temperature of 18°C and a high phase change latent heat of 230J / g, but also has good chemical stability and is not easy to decompose at high temperatures, so it can store electric heat through phase change, prevent rapid heat loss, improve energy utilization efficiency, and improve the efficiency of active deicing.
[0056] The use of silicon dioxide-copper double-shell coated hexadecane phase change microcapsules as photothermal response particles can effectively delay ice formation and actively remove ice during the day. In addition, the photothermal super-hydrophobic coating is formed by combining fluorinated silicon dioxide-copper double-shell coated hexadecane phase change microcapsules with terminal hydroxyl polydimethylsiloxane, so that the prepared composite coating not only has photothermal, electrothermal, and phase change energy storage characteristics, but also super-hydrophobicity makes it difficult for some pollutants to adhere to the surface, and has self-cleaning characteristics, which in turn improves the photothermal conversion effect, thereby improving the comprehensive performance and application potential of the composite coating.
[0057] (3) A phase-change energy storage composite coating having both photothermal and electrothermal properties according to the present invention,
[0058] The silica-coated n-hexadecane phase change microcapsules, silica-copper double-shell-coated n-hexadecane phase change microcapsules and fluorinated silica-copper double-shell-coated n-hexadecane phase change microcapsules contained in the coating can all utilize phase change to absorb or release heat; among them, the photothermal layer prepared by fluorinated silica-copper double-shell-coated n-hexadecane phase change microcapsules improves the utilization efficiency of solar energy by combining photothermal energy with phase change microcapsule energy storage; among them, the conductive layer prepared by silica-copper double-shell-coated n-hexadecane phase change microcapsules and graphite also improves the efficiency of electricity use by combining electric heating with phase change microcapsule energy storage; in addition, the phase change energy storage layer prepared by silica-copper double-shell-coated n-hexadecane phase change microcapsules is close to the substrate, which further maintains energy storage.
[0059] In short, the phase change microcapsules contained in the three coating layers can enable the coating to retain heat under hot and cold changes, reduce heat loss, and improve energy utilization efficiency, thereby regulating the surface temperature. Based on this characteristic, it can more effectively prolong the accumulation of ice and frost on the surface in a low temperature and high humidity environment, effectively improving the effect of delaying ice and frost.
[0060] (4) The present invention provides a phase-change energy storage composite coating with both photothermal and electric heating for use in all-weather anti-icing and de-icing. The phase-change energy storage composite coating with both photothermal and electric heating is a super-hydrophobic anti-icing and de-icing coating with high-efficiency photothermal and electric heating conversion and energy storage functions. It can be applied to the surface of outdoor equipment. The photothermal or electric heating conversion performance of the phase-change energy storage composite coating with both photothermal and electric heating can increase the surface temperature of the equipment to prevent icing. In addition, its hydrophobic property can prevent the adhesion of water and ice, thereby extending the service life of the equipment. In particular, it can cope with the problem of surface icing under extreme climatic conditions and ensure that the coating maintains effective anti-icing and de-icing functions at night, on cloudy days, and other time periods. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0062] Figure 1 The schematic diagram is a synthesis route of the silicon dioxide-coated n-hexadecane phase change microcapsules and the silicon dioxide-copper double shell-coated n-hexadecane phase change microcapsules of the present invention.
[0063] Figure 2 This is a SEM image of the silicon dioxide-coated n-hexadecane phase change microcapsules prepared in Example 1.
[0064] Figure 3This is a SEM image of the silicon dioxide-copper double-shell coated n-hexadecane phase change microcapsules prepared in Example 1.
[0065] Figure 4 This is a SEM image of the surface structure of a phase-change energy storage composite coating having both photothermal and electrothermal properties obtained in Example 1.
[0066] Figure 5 SiO 2 , n-hexadecane and infrared spectra of silica-coated n-hexadecane phase change microcapsules prepared in Example 1.
[0067] Figure 6 SiO 2 , X-ray powder diffraction patterns of the silica-coated n-hexadecane phase change microcapsules and the silica-copper double-shell-coated n-hexadecane phase change microcapsules prepared in Example 1.
[0068] Figure 7 This is the EDS spectrum analysis diagram of the silicon dioxide-copper double shell coated n-hexadecane phase change microcapsules prepared in Example 1.
[0069] Figure 8 This is a surface vertical motion adhesion test diagram of a phase-change energy storage composite coating with both photothermal and electrothermal properties obtained in Example 1.
[0070] Fig. 9 This is a surface water drop elasticity test diagram of a phase change energy storage composite coating with both photothermal and electrothermal properties obtained in Example 1.
[0071] Fig.10 This is an electric thermal cycle test diagram of a phase change energy storage composite coating with both photothermal and electric thermal properties obtained in Example 1.
[0072] Fig.11 This is a photothermal cycle test diagram of a phase-change energy storage composite coating with both photothermal and electrothermal properties obtained in Example 1.
[0073] Fig.12 This is a static delayed freezing test diagram of the photothermal super-hydrophobic energy storage coating prepared in Example 1 and a phase-change energy storage composite coating with both photothermal and electrothermal properties at low temperatures.
[0074] Fig.13 This is a photothermal deicing speed test diagram of a phase-change energy storage composite coating with both photothermal and electrothermal properties obtained in Example 1 under light.
[0075] Fig.14 This is a test diagram of the electric heating deicing speed of a phase change energy storage composite coating with both photothermal and electric heating prepared in Example 1 under a DC power supply. DETAILED DESCRIPTION
[0076] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0077] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. In the present invention, the singular forms "a", "said" and "the" used in the embodiments and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0078] The following describes the invention in conjunction with specific embodiments.
[0079] Example 1
[0080] A method for preparing a phase-change energy storage composite coating having both photothermal and electrothermal properties, characterized in that it comprises the following steps:
[0081] S1. Coating and forming phase change energy storage layer: Add hydroxyl-terminated polydimethylsiloxane and curing agent into n-hexane and stir to mix, then add silicon dioxide-coated n-hexadecane phase change microcapsules (recorded as nC 16 @SiO 2 ), mixed to form a slurry, and then sprayed on an aluminum plate polished with sandpaper and cleaned with isopropyl alcohol, and cured at 100°C for 2h to form a phase change energy storage layer; In this embodiment, the mass volume ratio of terminal hydroxyl polydimethylsiloxane, curing agent, silica-coated n-hexadecane phase change microcapsules and n-hexane is 3.5g:0.3g:1g:20mL;
[0082] Among them, nC 16 @SiO 2 The synthesis method comprises the following steps:
[0083] 1) Emulsification: After heating a mixed solution of anhydrous ethanol and deionized water to 35° C. in a water bath, n-hexadecane, hexadecyltrimethylammonium bromide and tetraethyl orthosilicate were added, and stirred and dispersed at a speed of 2500 rpm by a high-speed disperser for 10 min to form an oil-in-water emulsion; in this embodiment, the volume ratio of anhydrous ethanol to deionized water is 1:2; the mass ratio of n-hexadecane, hexadecyltrimethylammonium bromide and tetraethyl orthosilicate is 10:2:12; the mass volume ratio of n-hexadecane to the mixed solution is 10 g:280 mL;
[0084] 2) Polycondensation reaction: 2.5 mL of 25%-28% ammonia water was added to the oil-in-water emulsion obtained in the emulsification step at 35°C for 24 hours for polycondensation reaction, and then filtered, washed with petroleum ether and anhydrous ethanol for 3 times, and then washed with deionized water for 2 times, and then freeze-dried for 24 hours to obtain a white powder product, namely nC 16 @SiO 2 ; In this embodiment, the volume ratio of alkali to oil-in-water emulsion is 3:300.
[0085] S2, pasting copper foil and coating electric heat storage layer: paste copper foil electrodes on the two opposite edges of the surface of the phase change storage layer formed in step S1 and extend them outside the phase change storage layer; add hydroxyl-terminated polydimethylsiloxane and curing agent into n-hexane and stir to mix, then add silicon dioxide-copper double shell layer coated n-hexadecane phase change microcapsules (recorded as nC 16 @SiO 2- Cu) and graphite are mixed to form a slurry, and then the slurry is sprayed on the surface of the phase change energy storage layer to form an electric thermal energy storage layer; in this embodiment, the terminal hydroxyl polydimethylsiloxane, the curing agent, nC 16 @SiO 2- The mass volume ratio of Cu, graphite and n-hexane is 2 g: 0.2 g: 0.5 g: 0.2 g: 15 mL;
[0086] Among them, nC 16 @SiO 2- The synthesis method of Cu comprises the following steps:
[0087] 1) Sensitization: SnCl with a mass concentration of 1% 2 Add 12 mol / L hydrochloric acid to the solution, stir at 300 rpm for 5 min, add the silicon dioxide-coated n-hexadecane phase change microcapsules in step S1, stir and react for 10 min, and then filter and wash 3 times to obtain sensitized phase change microcapsules; nC 16 @SiO 2 SnCl 2 The mass volume ratio of solution and hydrochloric acid is 5g:100mL:4mL;
[0088] 2) Activation: Add the sensitized phase change microcapsules into a solution of PdCl at a concentration of 50 mg / L. 2 The activation reaction was carried out in the solution for 5 minutes, and after filtration and washing, the activated phase change microcapsules were obtained; in this embodiment, the sensitized phase change microcapsules were reacted with PdCl 2 The mass volume ratio of the solution is 1g:50mL;
[0089] 3) Chemical copper plating: The activated phase change microcapsules, copper sulfate pentahydrate, and EDTA were added to deionized water, and then sodium hypophosphite was added under stirring at a speed of 200 rpm to carry out chemical copper plating reaction for 60 minutes to obtain the nC 16 @SiO 2- In this embodiment, the mass volume ratio of copper sulfate pentahydrate, EDTA, activated phase change microcapsules, sodium hypophosphite and deionized water is 2g:1g:2g:3g:100mL.
[0090] S3, coating to form a photothermal super-hydrophobic energy storage coating: add terminal hydroxyl polydimethylsiloxane and curing agent to n-hexane and stir to mix, then add fluorinated silica-copper double-shell coated n-hexadecane phase change microcapsules, mix to form a slurry, and then spray the slurry on the surface of the electrothermal energy storage layer, and then cure it at 100°C for 6 hours to form a photothermal super-hydrophobic energy storage coating, that is, to obtain a phase change energy storage composite coating with both photothermal and electrothermal properties. In this embodiment, the particle size of graphite is 2μm-5μm. In this embodiment, the mass volume ratio of terminal hydroxyl polydimethylsiloxane, curing agent, fluorinated silica-copper double-shell coated n-hexadecane phase change microcapsules and n-hexane is 1g: 0.15g: 0.8g: 10mL;
[0091] Among them, the fluorinated nC 16 @SiO 2- The synthesis method of Cu is as follows: micro-etching the surface of the silicon dioxide-copper double-shell n-hexadecane phase change microcapsule is micro-etched by using a micro-etching liquid, dissolving tridecafluorooctyl triethoxysilane in anhydrous ethanol, and then adding the micro-etched silicon dioxide-copper double-shell n-hexadecane phase change microcapsule, stirring and dispersing, and then adding water, stirring and hydrolyzing for 2 hours, washing with ethanol after filtration, and then placing in a vacuum drying oven at 80° C. for 4 hours; in this embodiment, tridecafluorooctyl triethoxysilane, ethanol, nC 16 @SiO 2- The mass volume ratio of Cu and deionized water is 4 mL:200 mL:4 g:0.5 mL.
[0092] In this embodiment, the micro-etching solution includes sulfuric acid, hydrogen peroxide, sodium silicate and deionized water, and the mass ratio of sulfuric acid, hydrogen peroxide, sodium silicate and water is 5.5g:2.5g:0.08g:150mL.
[0093] In this embodiment, the curing agent in steps S1, S2 and S3 is component B of Dow Corning 184.
[0094] The schematic diagram of the synthesis route of silica-coated n-hexadecane phase change microcapsules and silica-copper double shell-coated n-hexadecane phase change microcapsules is shown in FIG. Figure 1 shown. Figure 1In the formula, CATB stands for the emulsifier hexadecyltrimethylammonium bromide and TEOS stands for tetraethyl orthosilicate.
[0095] Example 2
[0096] A method for preparing a phase-change energy storage composite coating having both photothermal and electrothermal properties, characterized in that it comprises the following steps:
[0097] S1. Coating and forming phase change energy storage layer: Add hydroxyl-terminated polydimethylsiloxane and curing agent into n-hexane and stir to mix, then add silicon dioxide-coated n-hexadecane phase change microcapsules (recorded as nC 16 @SiO 2 ), mixed to form a slurry, and then sprayed on an aluminum plate polished with sandpaper and cleaned with isopropyl alcohol, and cured at 90°C for 2.5h to form a phase change energy storage layer; In this embodiment, the mass volume ratio of terminal hydroxyl polydimethylsiloxane, curing agent, silica-coated n-hexadecane phase change microcapsules and n-hexane is 3g:0.2g:0.5g:15mL;
[0098] Among them, nC 16 @SiO 2 The synthesis method comprises the following steps:
[0099] 1) Emulsification: After heating a mixed solution of anhydrous ethanol and water to 30° C. in a water bath, n-hexadecane, hexadecyltrimethylammonium bromide and tetraethyl orthosilicate were added, and stirred and dispersed for 15 minutes at a speed of 2000 rpm using a high-speed disperser to form an oil-in-water emulsion; in this embodiment, the volume ratio of anhydrous ethanol to water is 1:1.5; the mass ratio of n-hexadecane, hexadecyltrimethylammonium bromide and tetraethyl orthosilicate is 8:1:10; the mass volume ratio of n-hexadecane to the mixed solution is 8 g:250 mL;
[0100] 2) Polycondensation reaction: Add 2 mL of 25%-28% ammonia water to the oil-in-water emulsion obtained in the emulsification step at 30°C for condensation reaction for 26 hours, then filter, wash twice with petroleum ether and anhydrous ethanol, wash once with deionized water, and then freeze-dry for 22 hours to obtain a white powder product, namely nC 16 @SiO 2 ; In this embodiment, the volume ratio of alkali to oil-in-water emulsion is 1:250.
[0101] S2, pasting copper foil and coating electric heat storage layer: paste copper foil electrodes on the two opposite edges of the surface of the phase change storage layer formed in step S1 and extend them outside the phase change storage layer; add hydroxyl-terminated polydimethylsiloxane and curing agent into n-hexane and stir to mix, then add silicon dioxide-copper double shell layer coated n-hexadecane phase change microcapsules (recorded as nC 16 @SiO2- Cu) and graphite are mixed to form a slurry, and then the slurry is sprayed on the surface of the phase change energy storage layer to form an electric thermal energy storage layer; in this embodiment, the terminal hydroxyl polydimethylsiloxane, the curing agent, nC 16 @SiO 2- The mass volume ratio of Cu, graphite and n-hexane is 1.5 g: 0.1 g: 0.3 g: 0.1 g: 10 mL;
[0102] Among them, nC 16 @SiO 2- The synthesis method of Cu comprises the following steps:
[0103] 1) Sensitization: SnCl with a mass concentration of 0.5% 2 Add 10 mol / L hydrochloric acid to the solution, stir at 250 rpm for 8 min, add the silicon dioxide coated n-hexadecane phase change microcapsules in step S1, stir and react for 5 min, then filter and wash twice to obtain sensitized phase change microcapsules; silicon dioxide coated n-hexadecane phase change microcapsules, SnCl 2 The mass volume ratio of solution and hydrochloric acid is 3g:90mL:3mL;
[0104] 2) Activation: Add the sensitized phase change microcapsules into a solution of PdCl at a concentration of 40 mg / L. 2 The activation reaction was carried out in the solution for 3 minutes, and after filtration and washing, the activated phase change microcapsules were obtained; in this embodiment, the sensitized phase change microcapsules were reacted with PdCl 2 The mass volume ratio of the solution is 0.5g:40mL;
[0105] 3) Chemical copper plating: The activated phase change microcapsules, copper sulfate pentahydrate, and EDTA were added to deionized water, and then sodium hypophosphite was added under stirring with a magnetic stirrer at a speed of 150 rpm to carry out chemical copper plating reaction for 70 minutes to obtain the nC 16 @SiO 2- In this embodiment, the mass volume ratio of copper sulfate pentahydrate, EDTA, activated phase change microcapsules, sodium hypophosphite and deionized water is 1g:0.5g:1g:2g:90mL.
[0106] S3, coating and forming a photothermal super-hydrophobic energy storage coating: add terminal hydroxyl polydimethylsiloxane and curing agent to n-hexane and stir to mix, then add fluorinated silica-copper double-shell coated n-hexadecane phase change microcapsules, mix to form a slurry, and then spray the slurry on the surface of the electrothermal energy storage layer, and then cure it at 90°C for 7h to form a photothermal super-hydrophobic energy storage coating, that is, to obtain a phase change energy storage composite coating with both photothermal and electrothermal properties. In this embodiment, the particle size of graphite is 2μm-5μm. In this embodiment, the mass volume ratio of terminal hydroxyl polydimethylsiloxane, curing agent, fluorinated silica-copper double-shell coated n-hexadecane phase change microcapsules and n-hexane is 0.5g:0.1g:0.5g:5mL;
[0107] Among them, the fluorinated nC 16 @SiO 2- The synthesis method of Cu is as follows: micro-etching the surface of the silicon dioxide-copper double-shell n-hexadecane phase change microcapsule is micro-etched by using a micro-etching liquid, dissolving tridecafluorooctyl triethoxysilane in anhydrous ethanol, and then adding the micro-etched silicon dioxide-copper double-shell n-hexadecane phase change microcapsule, stirring and dispersing, and then adding 0.5 mL of deionized water, stirring and hydrolyzing for 1.5 hours, washing with ethanol after filtration, and then placing in a vacuum drying oven at 75° C. for 5 hours; in this embodiment, tridecafluorooctyl triethoxysilane, ethanol, nC 16 @SiO 2- The mass volume ratio of Cu and deionized water is 3mL:180mL:3g:0.3mL.
[0108] In this embodiment, the micro-etching solution includes sulfuric acid, hydrogen peroxide, sodium silicate and deionized water, and the mass ratio of sulfuric acid, hydrogen peroxide, sodium silicate and water is 5g:2g:0.05g:100mL.
[0109] In this embodiment, the curing agent in steps S1, S2 and S3 is component B of Dow Corning 184.
[0110] Example 3
[0111] A method for preparing a phase-change energy storage composite coating having both photothermal and electrothermal properties, characterized in that it comprises the following steps:
[0112] S1. Coating and forming phase change energy storage layer: Add hydroxyl-terminated polydimethylsiloxane and curing agent into n-hexane and stir to mix, then add silicon dioxide-coated n-hexadecane phase change microcapsules (recorded as nC 16 @SiO 2), mixed to form a slurry, and then sprayed on an aluminum plate polished with sandpaper and cleaned with isopropyl alcohol, and cured at 110°C for 1.5h to form a phase change energy storage layer; In this embodiment, the mass volume ratio of terminal hydroxyl polydimethylsiloxane, curing agent, silica-coated n-hexadecane phase change microcapsules and n-hexane is 4g:0.5g:1.5g:25mL;
[0113] Among them, nC 16 @SiO 2 The synthesis method comprises the following steps:
[0114] 1) Emulsification: After heating a mixed solution of anhydrous ethanol and water to 40° C. in a water bath, n-hexadecane, hexadecyltrimethylammonium bromide and tetraethyl orthosilicate were added, and stirred and dispersed at a speed of 3000 rpm by a high-speed disperser for 5 minutes to form an oil-in-water emulsion; in this embodiment, the volume ratio of anhydrous ethanol to water is 1:3; the mass ratio of n-hexadecane, hexadecyltrimethylammonium bromide and tetraethyl orthosilicate is 12:2.5:15; the mass volume ratio of n-hexadecane to the mixed solution is 12 g:300 mL;
[0115] 2) Polycondensation reaction: 3 mL of 25%-28% ammonia water was added to the oil-in-water emulsion obtained in the emulsification step at 40°C for 26 hours of polycondensation reaction, and then filtered, washed with petroleum ether and anhydrous ethanol for 4 times, and then washed with deionized water for 3 times, and then freeze-dried for 26 hours to obtain a white powder product, namely nC 16 @SiO 2 ; In this embodiment, the volume ratio of alkali to oil-in-water emulsion is 5:350.
[0116] S2, pasting copper foil and coating electric heat storage layer: paste copper foil electrodes on the two opposite edges of the surface of the phase change storage layer formed in step S1 and extend them outside the phase change storage layer; add hydroxyl-terminated polydimethylsiloxane and curing agent into n-hexane and stir to mix, then add silicon dioxide-copper double shell layer coated n-hexadecane phase change microcapsules (recorded as nC 16 @SiO 2- Cu) and graphite are mixed to form a slurry, and then the slurry is sprayed on the surface of the phase change energy storage layer to form an electric thermal energy storage layer; in this embodiment, the terminal hydroxyl polydimethylsiloxane, the curing agent, nC 16 @SiO 2- The mass volume ratio of Cu, graphite and n-hexane is 2.5 g: 0.3 g: 0.8 g: 0.3 g: 20 mL;
[0117] Among them, nC 16 @SiO 2- The synthesis method of Cu comprises the following steps:
[0118] 1) Sensitization: SnCl with a mass concentration of 1.5% 2 Add 9 mol / L hydrochloric acid to the solution, stir at 350 rpm for 3 min, add the silicon dioxide-coated n-hexadecane phase change microcapsules in step S1, stir and react for 15 min, and then filter and wash 4 times to obtain sensitized phase change microcapsules; nC 16 @SiO 2 SnCl 2 The mass volume ratio of solution and hydrochloric acid is 8g:110mL:5mL;
[0119] 2) Activation: Add the sensitized phase change microcapsules into a 60 mg / L PdCl 2 The activation reaction was carried out in the solution for 8 minutes, and after filtration and washing, the activated phase change microcapsules were obtained; in this embodiment, the sensitized phase change microcapsules were reacted with PdCl 2 The mass volume ratio of the solution is 1.5g:60mL;
[0120] 3) Chemical copper plating: The activated phase change microcapsules, copper sulfate pentahydrate, and EDTA were added to deionized water, and then sodium hypophosphite was added under stirring at a speed of 250 rpm to carry out chemical copper plating reaction for 50 minutes to obtain the nC 16 @SiO 2- In this embodiment, the mass volume ratio of copper sulfate pentahydrate, EDTA, activated phase change microcapsules, sodium hypophosphite and water is 3g:2g:3g:4g:110mL.
[0121] S3, coating to form a photothermal super-hydrophobic energy storage coating: add terminal hydroxyl polydimethylsiloxane and curing agent to n-hexane and stir to mix, then add fluorinated silica-copper double-shell coated n-hexadecane phase change microcapsules, mix to form a slurry, and then spray the slurry on the surface of the electrothermal energy storage layer, and then cure it at 110°C for 5h to form a photothermal super-hydrophobic energy storage coating, that is, to obtain a phase change energy storage composite coating with both photothermal and electrothermal properties. In this embodiment, the particle size of graphite is 2μm-5μm. In this embodiment, the mass volume ratio of terminal hydroxyl polydimethylsiloxane, curing agent, fluorinated silica-copper double-shell coated n-hexadecane phase change microcapsules and n-hexane is 1.5g:0.2g:1.2g:15mL;
[0122] Among them, the fluorinated nC 16 @SiO 2-The synthesis method of Cu is as follows: micro-etching the surface of the silicon dioxide-copper double-shell n-hexadecane phase change microcapsule is micro-etched by using a micro-etching liquid, dissolving tridecafluorooctyl triethoxysilane in anhydrous ethanol, and then adding the micro-etched silicon dioxide-copper double-shell n-hexadecane phase change microcapsule, stirring and dispersing, and then adding water, stirring and hydrolyzing for 2.5 hours, washing with ethanol after filtration, and then placing in a vacuum drying oven at 85° C. for 3 hours; in this embodiment, tridecafluorooctyl triethoxysilane, ethanol, nC 16 @SiO 2- The mass volume ratio of Cu and deionized water is 5 mL:220 mL:5 g:0.8 mL.
[0123] In this embodiment, the micro-etching solution includes sulfuric acid, hydrogen peroxide, sodium silicate and deionized water, and the mass ratio of sulfuric acid, hydrogen peroxide, sodium silicate and water is 6g:3g:0.1g:200mL.
[0124] In this embodiment, the curing agent in steps S1, S2 and S3 is component B of Dow Corning 184.
[0125] Example 4
[0126] A method for preparing a phase-change energy storage composite coating having both photothermal and electrothermal properties, characterized in that it comprises the following steps:
[0127] S1. Coating and forming phase change energy storage layer: Add hydroxyl-terminated polydimethylsiloxane and curing agent into n-hexane and stir to mix, then add silicon dioxide-coated n-hexadecane phase change microcapsules (recorded as nC 16 @SiO 2 ), mixed to form a slurry, and then sprayed on an aluminum plate polished with sandpaper and cleaned with isopropyl alcohol, and cured at 95°C for 2.2h to form a phase change energy storage layer; In this embodiment, the mass volume ratio of terminal hydroxyl polydimethylsiloxane, curing agent, silica-coated n-hexadecane phase change microcapsules and n-hexane is 3.3g:0.3g:0.8g:18mL;
[0128] Among them, nC 16 @SiO 2 The synthesis method comprises the following steps:
[0129] 1) Emulsification: After heating a mixed solution of anhydrous ethanol and water to 32° C. in a water bath, n-hexadecane, hexadecyltrimethylammonium bromide and tetraethyl orthosilicate were added, and stirred and dispersed at a speed of 2400 rpm by a high-speed disperser for 7 minutes to form an oil-in-water emulsion; in this embodiment, the volume ratio of anhydrous ethanol to deionized water is 1:1.8; the mass ratio of n-hexadecane, hexadecyltrimethylammonium bromide and tetraethyl orthosilicate is 9:1.9:11; the mass volume ratio of n-hexadecane to the mixed solution is 9 g:260 mL;
[0130] 2) Polycondensation reaction: 2.2 mL of 25%-28% ammonia water was added to the oil-in-water emulsion obtained in the emulsification step at 32°C for 23 hours of polycondensation reaction, and then filtered, washed with petroleum ether and anhydrous ethanol for 3 times, and then washed with deionized water for 2 times, and then freeze-dried for 23 hours to obtain a white powder product, namely nC 16 @SiO 2 ; In this embodiment, the volume ratio of alkali to oil-in-water emulsion is 2:280.
[0131] S2, pasting copper foil and coating electric heat storage layer: paste copper foil electrodes on the two opposite edges of the surface of the phase change storage layer formed in step S1 and extend them outside the phase change storage layer; add hydroxyl-terminated polydimethylsiloxane and curing agent into n-hexane and stir to mix, then add silicon dioxide-copper double shell layer coated n-hexadecane phase change microcapsules (recorded as nC 16 @SiO 2- Cu) and graphite are mixed to form a slurry, and then the slurry is sprayed on the surface of the phase change energy storage layer to form an electric thermal energy storage layer; in this embodiment, the terminal hydroxyl polydimethylsiloxane, the curing agent, nC 16 @SiO 2- The mass volume ratio of Cu, graphite and n-hexane is 1.7 g: 0.1 g: 0.4 g: 0.2 g: 13 mL;
[0132] Among them, nC 16 @SiO 2- The synthesis method of Cu comprises the following steps:
[0133] 1) Sensitization: SnCl with a mass concentration of 0.8% 2 Add 12 mol / L hydrochloric acid to the solution, stir at 280 rpm for 7 min, add the silicon dioxide-coated n-hexadecane phase change microcapsules in step S1, stir and react for 8 min, and then filter and wash 3 times to obtain sensitized phase change microcapsules; nC 16 @SiO 2 SnCl 2 The mass volume ratio of solution and hydrochloric acid is 4g:95mL:4mL;
[0134] 2) Activation: Add the sensitized phase change microcapsules into a solution of PdCl at a concentration of 45 mg / L. 2 The activation reaction was carried out in the solution for 4 minutes, and after filtration and washing, the activated phase change microcapsules were obtained; in this embodiment, the sensitized phase change microcapsules were reacted with PdCl 2 The mass volume ratio of the solution is 0.8g:45mL;
[0135] 3) Chemical copper plating: The activated phase change microcapsules, copper sulfate pentahydrate, and EDTA were added to deionized water, and then sodium hypophosphite was added under stirring at a speed of 180 rpm to carry out chemical copper plating reaction for 65 minutes to obtain the nC 16 @SiO 2- In this embodiment, the mass volume ratio of copper sulfate pentahydrate, EDTA, activated phase change microcapsules, sodium hypophosphite and water is 1.5g:0.8g:1.5g:3g:95mL.
[0136] S3, coating and forming a photothermal super-hydrophobic energy storage coating: add terminal hydroxyl polydimethylsiloxane and curing agent to n-hexane and stir to mix, then add fluorinated silica-copper double-shell coated n-hexadecane phase change microcapsules, mix to form a slurry, and then spray the slurry on the surface of the electrothermal energy storage layer, and then cure it at 95°C for 6.5h to form a photothermal super-hydrophobic energy storage coating, that is, to obtain a phase change energy storage composite coating with both photothermal and electrothermal properties. In this embodiment, the particle size of graphite is 2μm-5μm. In this embodiment, the mass volume ratio of terminal hydroxyl polydimethylsiloxane, curing agent, fluorinated silica-copper double-shell coated n-hexadecane phase change microcapsules and n-hexane is 0.8g:0.13g:0.7g:8mL;
[0137] Among them, the fluorinated nC 16 @SiO 2- The synthesis method of Cu is as follows: micro-etching the surface of the silicon dioxide-copper double-shell n-hexadecane phase change microcapsule is micro-etched by using a micro-etching liquid, dissolving tridecafluorooctyl triethoxysilane in anhydrous ethanol, and then adding the micro-etched silicon dioxide-copper double-shell n-hexadecane phase change microcapsule, stirring and dispersing, and then adding deionized water, stirring and hydrolyzing for 1.8 hours, washing with ethanol after filtration, and then placing in a vacuum drying oven at 78° C. for 4.5 hours; in this embodiment, tridecafluorooctyl triethoxysilane, ethanol, nC 16 @SiO 2- The mass volume ratio of Cu and deionized water is 3.5 mL:190 mL:3.5 g:0.4 mL.
[0138] In this embodiment, the micro-etching solution includes sulfuric acid, hydrogen peroxide, sodium silicate and deionized water, and the mass ratio of sulfuric acid, hydrogen peroxide, sodium silicate and water is 5.3g:2.2g:0.06g:120mL.
[0139] In this embodiment, the curing agent in steps S1, S2 and S3 is component B of Dow Corning 184.
[0140] Example 5
[0141] A method for preparing a phase-change energy storage composite coating having both photothermal and electrothermal properties, characterized in that it comprises the following steps:
[0142] S1. Coating and forming phase change energy storage layer: Add hydroxyl-terminated polydimethylsiloxane and curing agent into n-hexane and stir to mix, then add silicon dioxide-coated n-hexadecane phase change microcapsules (recorded as nC 16 @SiO 2 ), mixed to form a slurry, and then sprayed on an aluminum plate polished with sandpaper and cleaned with isopropyl alcohol, and cured at 105°C for 1.8h to form a phase change energy storage layer; In this embodiment, the mass volume ratio of terminal hydroxyl polydimethylsiloxane, curing agent, silica-coated n-hexadecane phase change microcapsules and n-hexane is 3.8g:0.4g:1.2g:22mL;
[0143] Among them, nC 16 @SiO 2 The synthesis method comprises the following steps:
[0144] 1) Emulsification: After heating a mixed solution of anhydrous ethanol and deionized water to 38° C. in a water bath, n-hexadecane, hexadecyltrimethylammonium bromide and tetraethyl orthosilicate were added, and stirred and dispersed for 12 minutes at a speed of 2800 rpm using a high-speed disperser to form an oil-in-water emulsion; in this embodiment, the volume ratio of anhydrous ethanol to deionized water is 1:2.5; the mass ratio of n-hexadecane, hexadecyltrimethylammonium bromide and tetraethyl orthosilicate is 11:2.2:14; the mass volume ratio of n-hexadecane to the mixed solution is 11 g:290 mL;
[0145] 2) Polycondensation reaction: 2.7 mL of 25%-28% ammonia water was added to the oil-in-water emulsion obtained in the emulsification step at 38°C for 25 h of polycondensation reaction, and then filtered, washed twice with petroleum ether and anhydrous ethanol, and then washed twice with deionized water, and then freeze-dried for 25 h to obtain a white powder product, namely nC 16 @SiO 2 ; In this embodiment, the volume ratio of alkali to oil-in-water emulsion is 4:320.
[0146] S2, pasting copper foil and coating electric heat storage layer: paste copper foil electrodes on the two opposite edges of the surface of the phase change storage layer formed in step S1 and extend them outside the phase change storage layer; add hydroxyl-terminated polydimethylsiloxane and curing agent into n-hexane and stir to mix, then add silicon dioxide-copper double shell layer coated n-hexadecane phase change microcapsules (recorded as nC 16 @SiO 2- Cu) and graphite are mixed to form a slurry, and then the slurry is sprayed on the surface of the phase change energy storage layer to form an electric thermal energy storage layer; in this embodiment, the terminal hydroxyl polydimethylsiloxane, the curing agent, nC 16 @SiO 2- The mass volume ratio of Cu, graphite and n-hexane is 2.2 g: 0.2 g: 0.7 g: 0.3 g: 18 mL;
[0147] Among them, nC 16 @SiO 2- The synthesis method of Cu comprises the following steps:
[0148] 1) Sensitization: SnCl with a mass concentration of 1.3% 2 Add 12 mol / L hydrochloric acid to the solution, stir at 330 rpm for 4 min, add the silicon dioxide-coated n-hexadecane phase change microcapsules in step S1, stir and react for 12 min, and then filter and wash 3 times to obtain sensitized phase change microcapsules; nC 16 @SiO 2 SnCl 2 The mass volume ratio of solution and hydrochloric acid is 7g:105mL:4mL;
[0149] 2) Activation: Add the sensitized phase change microcapsules into a solution of PdCl at a concentration of 55 mg / L. 2 The activation reaction was carried out in the solution for 7 minutes, and after filtration and washing, the activated phase change microcapsules were obtained; in this embodiment, the sensitized phase change microcapsules were reacted with PdCl 2 The mass volume ratio of the solution is 1.2g:55mL;
[0150] 3) Chemical copper plating: The activated phase change microcapsules, copper sulfate pentahydrate, and EDTA were added to deionized water, and then sodium hypophosphite was added under stirring at a speed of 230 rpm to carry out chemical copper plating reaction for 55 minutes to obtain the nC 16 @SiO 2- In this embodiment, the mass volume ratio of copper sulfate pentahydrate, EDTA, activated phase change microcapsules, sodium hypophosphite and water is 2g:1.6g:2.5g:3.5g:105mL.
[0151] S3, coating and forming a photothermal super-hydrophobic energy storage coating: add terminal hydroxyl polydimethylsiloxane and curing agent to n-hexane and stir to mix, then add fluorinated silica-copper double-shell coated n-hexadecane phase change microcapsules, mix to form a slurry, and then spray the slurry on the surface of the electrothermal energy storage layer, and then cure it at 105°C for 5.5h to form a photothermal super-hydrophobic energy storage coating, that is, to obtain a phase change energy storage composite coating with both photothermal and electrothermal properties. In this embodiment, the particle size of graphite is 4μm. In this embodiment, the mass volume ratio of terminal hydroxyl polydimethylsiloxane, curing agent, fluorinated silica-copper double-shell coated n-hexadecane phase change microcapsules and n-hexane is 1.2g:0.18g:1.1g:13mL;
[0152] Among them, the fluorinated nC 16 @SiO 2- The synthesis method of Cu is as follows: micro-etching the surface of the silicon dioxide-copper double-shell n-hexadecane phase change microcapsule is micro-etched by using a micro-etching solution, dissolving tridecafluorooctyl triethoxysilane in anhydrous ethanol, and then adding the micro-etched silicon dioxide-copper double-shell n-hexadecane phase change microcapsule, stirring and dispersing, and then adding 0.5 mL of deionized water, stirring and hydrolyzing for 2.2 hours, washing with ethanol after filtration, and then placing in a vacuum drying oven at 83° C. for 3.5 hours; in this embodiment, tridecafluorooctyl triethoxysilane, ethanol, nC 16 @SiO 2- The mass volume ratio of Cu and deionized water is 4.5 mL:210 mL:4.5 g:0.7 mL.
[0153] In this embodiment, the micro-etching solution includes sulfuric acid, hydrogen peroxide, sodium silicate and water, and the mass ratio of sulfuric acid, hydrogen peroxide, sodium silicate and deionized water is 5.8g:2.7g:0.09g:180mL.
[0154] In this embodiment, the curing agent in steps S1, S2 and S3 is component B of Dow Corning 184.
[0155] Example 6
[0156] Application of the phase-change energy storage composite coating with both photothermal and electric heating obtained by the preparation method of any one of the phase-change energy storage composite coatings with both photothermal and electric heating in the above-mentioned embodiments 1 to 5 in all-weather anti-icing and de-icing. Applied to the surface of outdoor equipment, the surface temperature of the equipment is increased to prevent ice formation through the photothermal or electric heat conversion performance of the phase-change energy storage composite coating with both photothermal and electric heating, and its hydrophobic property can prevent the adhesion of water and ice, extend the service life of the equipment, and especially can cope with the problem of surface icing under extreme climatic conditions, and ensure that the coating maintains effective anti-icing and de-icing functions at night, cloudy days and other time periods.
[0157] Structural morphology characterization
[0158] (I) Morphological characterization by scanning electron microscopy
[0159] The silicon dioxide-coated n-hexadecane phase change microcapsules and silicon dioxide-copper double-shell-coated n-hexadecane phase change microcapsules prepared by the method for preparing a phase change energy storage composite coating with both photothermal and electrothermal properties in Example 1 were characterized by scanning electron microscopy (SEM) respectively. The SEM images of the silicon dioxide-coated n-hexadecane phase change microcapsules are shown in FIG. Figure 2 As shown in Figure 2, the SEM image of the SiO2-Cu double-shelled n-hexadecane phase change microcapsules is shown in Figure 2. Figure 3 shown.
[0160] Depend on Figure 2 It can be seen that the silicon dioxide-coated n-hexadecane phase change microcapsules are spherical in structure and have good coating uniformity. Figure 3 It can be seen that the SiO2-Cu double-shell coated n-hexadecane phase change microcapsules are spherical structures, and the copper particles are evenly distributed on the surface of the microcapsules.
[0161] The phase-change energy storage composite coating with both photothermal and electrothermal properties prepared in Example 1 was characterized by scanning electron microscopy (SEM). The microstructure of the surface of the phase-change energy storage composite coating is as follows: Figure 4 shown.
[0162] Figure 4 From the SEM image of the phase change energy storage composite coating, it can be seen that its surface microstructure is a nano-level microstructure. Therefore, the phase change energy storage composite coating can significantly change the surface contact angle and water wetting behavior, thereby achieving superhydrophobic behavior.
[0163] (II) Structural characterization by infrared spectroscopy
[0164] SiO 2 , n-hexadecane and the silicon dioxide-coated n-hexadecane phase change microcapsules prepared in Example 1 were characterized by infrared spectroscopy. Figure 5 shown. Figure 5 In the case of n-hexadecane@SiO 2 Refers to silica-coated n-hexadecane phase change microcapsules.
[0165] Depend on Figure 5 It can be seen from the infrared spectrum that the spectrum of the prepared silicon dioxide-coated n-hexadecane phase change microcapsules contains SiO 2 All the absorption peaks of the core material n-hexadecane indicate that the core material n-hexadecane is successfully absorbed by the shell SiO 2 Encapsulation, and the preparation process does not destroy the chemical properties of n-hexadecane.
[0166] (III) Structural characterization by X-ray powder diffraction
[0167] SiO 2 , and the silicon dioxide-coated n-hexadecane phase change microcapsules and the silicon dioxide-copper double shell-coated n-hexadecane phase change microcapsules prepared in Example 1 were characterized by X-ray powder diffraction, respectively. Figure 6 shown. Figure 6 In the case of n-hexadecane@SiO 2 Refers to silicon dioxide coated hexadecane phase change microcapsules, hexadecane@SiO 2 @Cu refers to the silica-copper double-shell coated n-hexadecane phase change microcapsules.
[0168] Depend on Figure 6 The results of the X-ray powder diffraction test show that the diffraction peaks of n-hexadecane were found in both the silica-coated n-hexadecane phase change microcapsules and the silica-copper double-shelled n-hexadecane phase change microcapsules, indicating that the crystal structure of n-hexadecane was retained after the composite shell formation process. The X-ray powder diffraction pattern of the silica-coated n-hexadecane phase change microcapsules has a broad and low diffraction peak at 2θ=22°, indicating that the silica shell has an amorphous structure. The X-ray powder diffraction of the silica-copper double-shelled n-hexadecane phase change microcapsules showed three peaks of elemental copper, and the surface of the shell layer was successfully plated with copper.
[0169] (IV) Structural characterization by EDS spectrum analysis
[0170] The silicon dioxide-copper double-shell n-hexadecane phase change microcapsules prepared in Example 1 were subjected to EDS spectrum analysis to obtain element mapping spectra of O, Si and Cu, as shown in FIG. Figure 7 As shown. Figure 7 It can be seen that the silica-copper double-shell coated n-hexadecane phase change microcapsules prepared in Example 1 successfully completed the double-shell coating of the silica shell and the copper shell.
[0171] Performance Testing
[0172] (I) Vertical movement adhesion test of coating surface
[0173] The phase-change energy storage composite coating with both photothermal and electrothermal properties prepared in Example 1 was subjected to a vertical motion adhesion test on the coating surface. Figure 8 shown.
[0174] Depend on Figure 8 It can be seen that the vertical manipulation behavior of water droplets on the phase-change energy storage composite coating with both photothermal and electrothermal properties prepared by the present invention can be successfully separated in the end, indicating that the adhesion between the water droplets and the surface of the phase-change energy storage composite coating is relatively small.
[0175] (II) Water drop elasticity test on coating surface
[0176] The phase-change energy storage composite coating with both photothermal and electrothermal properties prepared in Example 1 was subjected to a water drop drop elasticity test on the coating surface. Fig. 9 shown.
[0177] Depend on Fig. 9 It can be seen that the low adhesion and excellent repellent properties of the surface of the phase-change energy storage composite coating with both photothermal and electrothermal properties prepared by the present invention enable a 10 μL water droplet to bounce continuously for more than 2 times from a height of 20 mm.
[0178] (III) Electrothermal cycle test of coating
[0179] The phase-change energy storage composite coating with both photothermal and electrothermal properties prepared in Example 1 was subjected to an electrothermal cycle test under the conditions of a DC power supply of 24V and 0.2A. Fig.10 shown.
[0180] Depend on Fig.10 It can be seen that the phase-change energy storage composite coating with both photothermal and electrothermal properties prepared by the present invention has a very high photothermal cycle stability.
[0181] (IV) Photothermal cycle test of coating
[0182] The phase-change energy storage composite coating with both photothermal and electrothermal properties prepared in Example 1 was heated to 100 mW / cm 2 The light-heat cycle test was carried out under the conditions of Fig.11 shown.
[0183] Depend on Fig.11 It can be seen that the phase-change energy storage composite coating with both photothermal and electrothermal properties prepared by the present invention has very high electrothermal cycle stability.
[0184] (V) Static icing delay test of coating at low temperature
[0185] The photothermal super-hydrophobic energy storage coating prepared in Example 1 and a phase-change energy storage composite coating with both photothermal and electrothermal properties were subjected to static freezing delay tests at -22 degrees Celsius. Fig.12 shown. Fig.12 In the embodiment, the “phase-change energy storage composite coating having both photothermal and electric heating properties” is a phase-change energy storage composite coating having both photothermal and electric heating properties obtained in Example 1.
[0186] Depend on Fig.12It can be seen that the photothermal super-hydrophobic energy storage coating prepared in Example 1 delays freezing for 37 seconds at -22 degrees Celsius, while the phase-change energy storage composite coating with both photothermal and electric heating prepared in Example 1 can delay freezing for up to 702 seconds at -22 degrees Celsius. Therefore, the phase-change energy storage composite coating with both photothermal and electric heating prepared in the present invention has a significant effect on delaying the freezing process of surface water droplets, and can effectively delay freezing under extreme climate conditions.
[0187] (VI) Photothermal deicing speed test of coating
[0188] The phase-change energy storage composite coating with both photothermal and electrothermal properties prepared in Example 1 was heated to 100 mW / cm 2 The speed test of photothermal deicing is carried out under illumination, such as Fig.13 shown.
[0189] Depend on Fig.13 It can be seen that the phase-change energy storage composite coating with both photothermal and electrothermal properties prepared by the present invention has a thermal conductivity of 100 mW / cm 2 The ice droplets can melt quickly after 120 seconds under light.
[0190] (VII) Electrical deicing speed test of coating
[0191] The phase-change energy storage composite coating with both photothermal and electrothermal properties prepared in Example 1 was subjected to an electrothermal deicing speed test under a 24V, 0.02A DC power supply. Fig.14 shown.
[0192] Depend on Fig.14 It can be seen that the phase-change energy storage composite coating with both photothermal and electric heating prepared in the present invention can quickly melt ice droplets under a DC power supply of 24V and 0.02A within 95s. Therefore, the phase-change energy storage composite coating with both photothermal and electric heating of the present invention has a high efficiency of deicing rate.
[0193] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing a phase-change energy storage composite coating with both photothermal and electrothermal properties, characterized in that: The following steps are involved: S1. Coating and forming a phase change energy storage layer: coating a slurry containing silicon dioxide-coated n-hexadecane phase change microcapsules on a substrate, and then curing and forming a phase change energy storage layer; S2, pasting copper foil and coating an electric thermal energy storage layer: pasting copper foil electrodes on two opposite edges of the surface of the phase change energy storage layer formed in step S1 and extending them to the outside of the phase change energy storage layer, and then coating the surface of the phase change energy storage layer with a slurry containing silicon dioxide-copper double-shell coated n-hexadecane phase change microcapsules and graphite to form an electric thermal energy storage layer; S3. Coating and forming a photothermal super-hydrophobic energy storage coating: coating the surface of the electrothermal energy storage layer formed in step S2 with a slurry containing fluorinated silica-copper double-shell-coated n-hexadecane phase change microcapsules, and then curing and forming the photothermal super-hydrophobic energy storage coating, thereby obtaining the phase change energy storage composite coating having both photothermal and electrothermal properties.
2. The method for preparing a phase-change energy storage composite coating having both photothermal and electrothermal properties as claimed in claim 1, characterized in that: In the step S1, a slurry containing silicon dioxide-coated n-hexadecane phase change microcapsules is coated on an aluminum plate that has been sanded and cleaned with isopropyl alcohol, and then cured to form a phase change energy storage layer; the synthesis method of the silicon dioxide-coated n-hexadecane phase change microcapsules comprises the following steps: 1) Emulsification: After heating a mixture of anhydrous ethanol and water, n-hexadecane, hexadecyltrimethylammonium bromide and tetraethyl orthosilicate are added to disperse and form an oil-in-water emulsion; 2) Polycondensation reaction: adding alkali to the oil-in-water emulsion obtained in step 1) to carry out polycondensation reaction, and then filtering, washing and drying to obtain the silicon dioxide-coated n-hexadecane phase change microcapsules.
3. The method for preparing a phase-change energy storage composite coating having both photothermal and electrothermal properties as claimed in claim 2, characterized in that: In the emulsification step, the volume ratio of anhydrous ethanol to water is 1:(1.5-3); the mass ratio of n-hexadecane, hexadecyltrimethylammonium bromide and tetraethyl orthosilicate is (8-12):(1-2.5):(10-15); the mass volume ratio of n-hexadecane to the mixed solution is (8-12) g:(250-300) mL; the heating is heated to 30° C.-40° C. by water bath heating; the dispersion is stirred at a speed of 2000 rpm-3000 rpm for 5 min-15 min by a high-speed disperser; and / or In the polycondensation reaction step, ammonia water with a mass concentration of 25%-28% is added to the water-in-oil emulsion obtained in the emulsification step at 30°C-40°C, and the polycondensation reaction is carried out for 22h-26h, followed by suction filtration, washing with petroleum ether and anhydrous ethanol for 2-4 times respectively, and then washing with deionized water for 1-3 times, and then freeze-drying for 22h-26h to obtain a white powder product, namely the silicon dioxide-coated n-hexadecane phase change microcapsule; the volume ratio of the alkali to the water-in-oil emulsion is (1-5): (250-350).
4. The method for preparing a phase-change energy storage composite coating having both photothermal and electrothermal properties as claimed in claim 1, characterized in that: In step S2, the synthesis method of silicon dioxide-copper double shell coated n-hexadecane phase change microcapsules comprises the following steps: 1) Sensitization: adding hydrochloric acid to the SnCl2 solution and mixing, adding the silicon dioxide-coated n-hexadecane phase change microcapsules prepared in step S1 to react, thereby obtaining sensitized phase change microcapsules; 2) Activation: adding the sensitized phase change microcapsules into a PdCl2 solution for activation reaction, and obtaining activated phase change microcapsules after filtration and deionized water washing; 3) Chemical copper plating: The activated phase change microcapsules, copper sulfate pentahydrate and EDTA are added into water, and then sodium hypophosphite is added under stirring to carry out chemical copper plating reaction, so as to obtain the silicon dioxide-copper double shell layer coated n-hexadecane phase change microcapsules.
5. The method for preparing a phase-change energy storage composite coating having both photothermal and electrothermal properties as claimed in claim 4, characterized in that: In the sensitization step, hydrochloric acid with a concentration of 9 mol / L-12 mol / L is added to a SnCl2 solution with a mass concentration of 0.5%-1.5%, and after stirring for 3 min-8 min at 250 rpm-350 rpm, the silicon dioxide-coated n-hexadecane phase change microcapsules in step S1 are added, and the mixture is stirred for reaction for 5 min-15 min, and then filtered and washed 2-4 times to obtain sensitized phase change microcapsules; the mass volume ratio of the silicon dioxide-coated n-hexadecane phase change microcapsules, the SnCl2 solution and the hydrochloric acid is (3-8) g: (90-110) mL: (3-5) mL; and / or In the activation step, the mass volume ratio of the sensitized phase change microcapsules to the PdCl2 solution is (0.5-1.5) g: (40-60) mL; the concentration of the PdCl2 solution is 40 mg / L-60 mg / L, and the activation time is 3 min-8 min; and / or In the chemical copper plating step, the mass volume ratio of the copper sulfate pentahydrate, EDTA, activated phase change microcapsules, sodium hypophosphite and water is (1-3) g: (0.5-2) g: (1-3) g: (2-4) g: (90-110) mL; the stirring speed is 150 rpm-250 rpm; and the chemical copper plating reaction time is 50 min-70 min.
6. The method for preparing a phase-change energy storage composite coating having both photothermal and electrothermal properties as claimed in claim 1, characterized in that: In the step S3, the synthesis method of the fluorinated silica-copper double-shell n-hexadecane phase change microcapsules is as follows: micro-etching the surface of the silica-copper double-shell n-hexadecane phase change microcapsules with a micro-etching solution, dissolving tridecafluorooctyl triethoxysilane in anhydrous ethanol, then adding the micro-etched silica-copper double-shell n-hexadecane phase change microcapsules, stirring and dispersing, then adding water, stirring and hydrolyzing for 1.5h-2.5h, filtering and washing with ethanol, and then drying in a vacuum drying oven at 75°C-85°C for 3h-5h; and / or The mass volume ratio of tridecafluorooctyl triethoxysilane, ethanol, silicon dioxide-copper double shell coated hexadecane phase change microcapsules, and water is (3-5) mL: (180-220) mL: (3-5) g: (0.3-0.8) mL; and / or The micro-etching solution comprises sulfuric acid, hydrogen peroxide, sodium silicate and water, and the mass ratio of the sulfuric acid, hydrogen peroxide, sodium silicate and water is (5-6) g: (2-3) g: (0.05-0.1) g: (100-200) mL.
7. The method for preparing a phase-change energy storage composite coating having both photothermal and electrothermal properties as claimed in claim 1, characterized in that: In the step S1, coating and forming a phase change energy storage layer: adding hydroxy-terminated polydimethylsiloxane and a curing agent into n-hexane and stirring and mixing, then adding silicon dioxide-coated n-hexadecane phase change microcapsules, mixing to form the slurry, then spraying the slurry, and curing at 90° C.-110° C. for 1.5 h-2.5 h to form a phase change energy storage layer; In the step S2, copper foil is pasted and an electric thermal energy storage layer is coated: copper foil electrodes are pasted at two opposite edges of the surface of the phase change energy storage layer formed in step S1 and extended to the outside of the phase change energy storage layer; terminal hydroxyl polydimethylsiloxane and a curing agent are added to n-hexane and stirred and mixed, and then silicon dioxide-copper double-shell coated n-hexadecane phase change microcapsules and graphite are added to mix to form the slurry, and then the slurry is sprayed on the surface of the phase change energy storage layer to form the electric thermal energy storage layer; In the step S3, a photothermal super-hydrophobic energy storage coating is coated: terminal hydroxyl polydimethylsiloxane and a curing agent are added to n-hexane and stirred and mixed, and then fluorinated silica-copper double-shell coated n-hexadecane phase change microcapsules are added to form the slurry, and then the slurry is sprayed on the surface of the electrothermal energy storage layer, and then cured at 90°C-110°C for 5h-7h to form the photothermal super-hydrophobic energy storage coating, so as to obtain the phase change energy storage composite coating with both photothermal and electrothermal properties.
8. The method for preparing a phase-change energy storage composite coating having both photothermal and electrothermal properties as claimed in claim 7, characterized in that: The curing agent in steps S1, S2 and S3 is component B of Dow Corning 184; In the step S1, the mass volume ratio of the terminal hydroxyl polydimethylsiloxane, the curing agent, the silicon dioxide-coated n-hexadecane phase change microcapsules and n-hexane is (3-4) g: (0.2-0.5) g: (0.5-1.5) g: (15-25) mL; In the step S2, the mass volume ratio of the hydroxy-terminated polydimethylsiloxane, the curing agent, the silicon dioxide-copper double-shell coated n-hexadecane phase change microcapsules, the graphite and the n-hexane is (1.5-2.5) g: (0.1-0.3) g: (0.3-0.8) g: (0.1-0.3) g: (10-20) mL; In the step S3, the mass volume ratio of the hydroxy-terminated polydimethylsiloxane, the curing agent, the fluorinated silica-copper double-shell coated n-hexadecane phase change microcapsules and n-hexane is (0.5-1.5) g: (0.1-0.2) g: (0.5-1.2) g: (5-15) mL; In the step S2, the particle size of the graphite is 1 μm-5 μm.
9. A phase-change energy storage composite coating with both photothermal and electrothermal properties, characterized in that: The composite coating is prepared by the method for preparing a phase-change energy storage coating having both photothermal and electrothermal properties as described in any one of claims 1 to 8.
10. Application of the phase-change energy storage composite coating with both photothermal and electric heating obtained by the preparation method of the phase-change energy storage composite coating with both photothermal and electric heating as described in any one of claims 1 to 8 in all-weather anti-icing and deicing.
Citation Information
Patent Citations
Photo-thermal response super-hydrophobic anti-icing composite coating layer and preparation method thereof
CN114058224A
An environmentally friendly super-hydrophobic anti-icing and deicing material with efficient light-heat conversion and a preparation method thereof
CN116790186B
Super-hydrophobic electric heating anti-icing / deicing coating material and preparation method thereof
CN116554783A
Phase-change wave-transparent electric heating coating, coating and preparation method and application of phase-change wave-transparent electric heating coating
CN118359976A
Preparation method of photo-thermal energy storage super-hydrophobic all-weather anti-icing coating
CN119101417A
Cited By
Low-temperature phase-change microcapsule super-hydrophobic anti-icing coating and preparation method thereof
CN120290092A